Fetal IgG specificities against Trypanosoma cruzi antigens in infected newborns. - Reyes, M B (1990)
A panel of Trypanosoma cruzi antigens produced by recombinant DNA techniques was used to analyze the IgM and IgG specificities present in sera from 22 mothers with chronic Chagas disease and their newborn infants. Ten of the newborns were congenitally infected and the other 12 children were healthy. While in most cases IgG specificities in the newborns mirrored those of their mothers, congenitally infected newborns had, in addition, IgG specificities that were undetectable in their mothers. The new IgG specificities observed most frequently were against a shed acute-phase antigen (SAPA), and less frequently, against other nine different parasite antigens. Thus, SAPA is able to identify new fetal IgGs because antibodies against this antigen are generated during the acute phase of the infection and not in their chronically infected mothers. Sera from congenital cases also had IgMs against several parasite antigens, but again, SAPA was the most frequently detected. Neither IgMs nor new IgG specificities were detected in healthy children born to mothers with Chagas disease. We conclude that individual antigens can be used to detect new IgG specificities present in the cord blood from infected newborns. Furthermore, detection of IgMs and new fetal IgGs with recombinant antigens may be used to sort out congenitally infected infants from uninfected ones, a method that might be applied to other infectious diseases.